Feeling nurse after the passing of a loved one - Fernández, Alba Rosa (Investigación y Educación en Enfermería, 2010)
With 14 years of university graduate as a nurse, the author expe-rienced the pain, sorrow, loss, and uncertainty in illness and death of a loved one. Knowledge and experience gotten in her profes-sional life were not enough to face these feelings which became pain, guilt, and reality denial. From her personal experience she rebuilt the nurse feelings to her mother’s death: that one, a tiny woman but of great character who with only 54 years old faced a terminal cancer. Impotence during the diseases course, the loss, grief, denial, anger, depression, acceptance and death made her understand the nursing role in critical situations that involve loved ones.